2013
DOI: 10.5558/tfc2013-038
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thinning on carbon stocks and fluxes in a Chinese arborvitae plantation

Abstract: China has extensive areas of forest plantations that sequester and store large quantities of carbon. However, the rate of carbon sequestration by Chinese arborvitae (Platycladus orientalis Linn. Franco) is unknown. This research looks at carbon stocks and fluxes in forest vegetation, soil and litter seven years after thinning Chinese arborvitae in order to evaluate the effect of thinning levels on carbon sequestration. At 22 years, the plots were reduced from 5900 to 4100 and 3000 trees per hectare in three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In this investigation, as soil depth increased, soil carbon storage under various thinning intensities declined. Additionally, surface layer soil bulk density is higher than bottom layer soil bulk density, which is consistent with earlier research and is linked to the action of plant roots and soil organisms that reduce soil depth-related carbon storage [52,53]. When the thinning intensity is 22%, soil carbon storage is improved, and ecosystem carbon storage can be significantly increased.…”
Section: Effect Of Thinning On Soil Carbonsupporting
confidence: 89%
“…In this investigation, as soil depth increased, soil carbon storage under various thinning intensities declined. Additionally, surface layer soil bulk density is higher than bottom layer soil bulk density, which is consistent with earlier research and is linked to the action of plant roots and soil organisms that reduce soil depth-related carbon storage [52,53]. When the thinning intensity is 22%, soil carbon storage is improved, and ecosystem carbon storage can be significantly increased.…”
Section: Effect Of Thinning On Soil Carbonsupporting
confidence: 89%
“…In addition, management practices, such tree thinning and slash-burning, which are implemented in planted pine forests exert different effects on soil carbon. Studies have reported that management practices such as prescribed fire, mechanical treatment, and thinning do not affect soil carbon stock density (Boerner et al 2008;Liang et al 2013;Nilsen and Strand 2008). However, other studies have reported that management practices do affect soil carbon stock density of planted forests (Tian et al 2010;Wu et al 2013).…”
Section: Soil Carbon Stock Densitymentioning
confidence: 99%
“…The density of dry wood of Pinus massoniana in the same area and of the same age is 346.6 kg•m -3 , the dry wood density of Pinus elliotti is 298.9 kg•m -3 [4]; Pinus massoniana's trunk, leaf, branch and root accounted for 65.1%, 11.8%, 10.5%, and 12.6% of dry weight of biomass [5], respectively. The level of carbon was 51.614%, 44.617%, 47.563%, and 50.737% [6], respectively. And Pinus elliotti's trunk, leaf, branch and root accounted for 63.8 %, 11.2%, 12.9%, and 12.1% of dry weight of biomass [5], respectively, The level of carbon was 54.786%, 59.33%, 55.59%, and 56.311% respectively [7].…”
Section: Methodsmentioning
confidence: 98%
“…The level of carbon was 51.614%, 44.617%, 47.563%, and 50.737% [6], respectively. And Pinus elliotti's trunk, leaf, branch and root accounted for 63.8 %, 11.2%, 12.9%, and 12.1% of dry weight of biomass [5], respectively, The level of carbon was 54.786%, 59.33%, 55.59%, and 56.311% respectively [7].…”
Section: Methodsmentioning
confidence: 98%